Book Review: Islam and Blackamerican: Looking Toward the Third Resurrection - Al-Aidrus, Ajmal (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Book Review: Islam and Blackamerican: Looking Toward the Third Resurrection